Development of a prototype smart waste bins / Afiqah Zafirah Zakaria - Zakaria, Afiqah Zafirah (2023)
With the ever-increasing population, urbanization, migration issues, and change in lifestyle, municipal solid waste generation levels are increasing significantly. Waste management has been a crucial issue to be considered. The current smart bins in market that are used not sophisticated enough to achieve robust and efficient waste management mechanism. Hence, there is a need to improve the current smart bins to work more efficiency by using Ultrasonic sensor and Arduino system. Through this project, student is required to develop an Arduino system and design a new smart bin integrated with an Ultrasonic sensor HC-SR04 with Arduino by using state-of-art SolidWorks 2019. The use of sensors on this bin will detect the user holding the trash and automatic the dustbin door will open. Other than that, the buzzer that has been connected to the Arduino will emit a sound when it detects there is garbage dumped outside the bin. The designed smart bins will be fabricated (prototype) as a proof of concept. Analytical and finite element analysis of the critical parts shall be carried out. This project shall assist the user by reducing energy required with the reducing the operation time.